2010
DOI: 10.1101/lm.1962010
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporter 3 is involved in learned fear and extinction, but not in innate fear

Abstract: Synaptically released Zn2+ is a potential modulator of neurotransmission and synaptic plasticity in fear-conditioning pathways. Zinc transporter 3 (ZnT3) knock-out (KO) mice are well suited to test the role of zinc in learned fear, because ZnT3 is colocalized with synaptic zinc, responsible for its transport to synaptic vesicles, highly enriched in the amygdala-associated neural circuitry, and ZnT3 KO mice lack Zn 2+ in synaptic vesicles. However, earlier work reported no deficiency in fear memory in ZnT3 KO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 45 publications
10
52
0
Order By: Relevance
“…The ZnT3KO phenotype complements recent reports supporting a role for synaptic zinc in cognition (33,34,41,42). Furthermore, the associated deficit in Erk signaling in ZnT3KO mice, which we show is required in the MF pathway for contextual discrimination, suggests a possible molecular mechanism for the memory defects.…”
Section: Discussionsupporting
confidence: 87%
“…The ZnT3KO phenotype complements recent reports supporting a role for synaptic zinc in cognition (33,34,41,42). Furthermore, the associated deficit in Erk signaling in ZnT3KO mice, which we show is required in the MF pathway for contextual discrimination, suggests a possible molecular mechanism for the memory defects.…”
Section: Discussionsupporting
confidence: 87%
“…ZnT3 probably contributes to the prevention of aging-related cognitive loss, because ZnT3 expression levels fall with age (1) and in patients with Alzheimer's disease (1, 34) or Parkinson's disease dementia (446). Consistent with these results, aged Znt3-KO mice exhibit deficits in learning and memory (1,269,377). However, young Znt3-KO mice were first reported to show almost no obvious phenotypes without slightly higher thresholds to seizures than wild-type mice, despite the observation that synaptic zinc is essentially absent (59).…”
Section: Znt3supporting
confidence: 72%
“…This protein is responsible for the accumulation of free zinc in glutamatecontaining vesicles found in the hippocampus and cortex (Gower-Winte and Levenson 2012). The SLC30A3 gene is expressed in brain regions important for cognitive development and development of different kinds of memory, such as the hippocampus, cerebral cortex, and amygdale (Seve et al 2004), and ZnT3 knock-out mice exhibit cognitive loss, alterations in memory and may represent a phenocopy for memory deficits of Alzheimer's disease (Adlard et al 2010;Martel et al 2010;. Despite the identification of locations important for studies related to memory, no previous work has identified the potential neurobiological influences and phenotypic consequences of genetic polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…The zinc transporter gene SLC30A3 is expressed in regions of the brain that are important for steps in memory formation, specially the cerebral cortex and hippocampus (Seve et al 2004;Frederickson et al 2005). Besides, data from experimental studies addressing the effect of ZnT3 ablation in ZnT3 knock-out mice demonstrated that these animals exhibit age-dependent deficits in learning and memory, leading a cognitive loss (Adlard et al 2010), abnormalities in associative fear memory and extinction (Martel et al 2010), and that ZnT3 is required for hippocampus-dependent memory . Considering the relevance of SLC30A3 gene on memory and cognition, two commonly occurring SNPs in this gene, rs11126936 (A[G) and rs73924411 (C[T), were selected for analysis.…”
Section: Introductionmentioning
confidence: 99%